Implementasi dan Pelatihan SIWAREK serta Solar Home System bagi Pokdarwis Opak Grembyangan - Emerita Setyowati; Sunneng Sandino Berutu; Susi Siswati (Jurnal Atma Inovasia, 2026)
The Tourism Awareness Group or Kelompok Sadar Wisata (Pokdarwis) of Mutihan, Madurejo Village, Prambanan, is pioneering the development of a tourism area along the Opak River. The main challenges faced include the lack of lighting facilities and difficulties in operating food stalls, although the buildings are already available. The community service team, in collaboration with local partners, initiated two main programs: the installation of a Solar Home System (SHS) to provide access to clean energy and reduce dependency on the state electricity grid (PLN), and training on financial management and digitalization for stall operations. The implementation methods included program socialization, financial management training, development of a stall information system, SHS installation, SHS operation training, as well as program monitoring and evaluation. As a result, a stall financial system named Sistem Informasi Keuangan Warung Opak (SIWAREK) was developed, and two SHS units were installed at the tourism site to supply renewable energy. The financial management and information system training provide a strong foundation for Pokdarwis to operate the food stalls. The SHS can be utilized for night lighting, charging visitors’ mobile phones and laptops, and also serve as a tourism icon showcasing the use of renewable energy